2010
DOI: 10.1186/1746-1340-18-24
|View full text |Cite
|
Sign up to set email alerts
|

The attrition rate of licensed chiropractors in California: an exploratory ecological investigation of time-trend data

Abstract: BackgroundThe authors hypothesized the attrition rate of licensed chiropractors in California has gradually increased over the past several decades. "Attrition" as determined for this study is defined as a loss of legal authority to practice chiropractic for any reason during the first 10 years after the license was issued. The percentage of license attrition after 10 years was determined for each group of graduates licensed in California each year between 1970 and 1998. The cost of tuition, the increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This perception would stand in contrast to a retrospective analysis [28] of licensed chiropractors in California. Here, alarmingly, the authors identified that the attrition in the first 10 years of practice rose from 10% to 25% in the past decade.…”
Section: Literature Reviewmentioning
confidence: 74%
See 1 more Smart Citation
“…This perception would stand in contrast to a retrospective analysis [28] of licensed chiropractors in California. Here, alarmingly, the authors identified that the attrition in the first 10 years of practice rose from 10% to 25% in the past decade.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Here, alarmingly, the authors identified that the attrition in the first 10 years of practice rose from 10% to 25% in the past decade. The authors hypothesized that the rising attrition rate of chiropractors may be linked to a number of forces such as changes in population, an oversupply of chiropractors, changes in reimbursement, the cost of education, and chiropractors' general dissatisfaction with their own profession [28]. In addition, data from a recent pilot study [29] exploring the attitudes of non-practicing chiropractors suggest that business ethics, overhead expenses and salaries were contributing factors of attrition in the chiropractic profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the province of Ontario Canada, the number of practicing chiropractors doubled from 1990 to 2004 [ 32 ]. Similar trends in the supply of licensed chiropractors occurred in the state of California from 1970 to 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends in the supply of licensed chiropractors occurred in the state of California from 1970 to 1998. Foreman and Stahl [ 32 ] noted that during this period, the number of licensed chiropractors within the state of California increased by 170%. This represented a significant increase from the general population that expanded by 65% during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…It is unrealistic to believe the attrition rate can be lowered to this degree as attrition occurs for a variety of reasons, including job elimination, maternity, death, disability, or illness. Other professions such as teaching, nursing, chiropractic, and physical therapy show attrition rates between 20 and 40% (Struber, 2003;Eggen, 2012;Foreman and Stahl, 2010). The reports by Doyle and Freeman and by Bennett and Steiger would suggest that there will be a lowering of the attrition rate, but whether attrition rates even as low as the 20% level can be reached cannot yet be determined.…”
Section: Workforce Projectionsmentioning
confidence: 99%